Pengembangan Bahan Ajar Teks Anekdot Berbasis Aplikasi TikTok pada Siswa Kelas X SMA Istiqlal Delitua - Razita Dayana; Rina Deviantyri; Edi Sahputra (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The research that has been carried out is entitled "Development of Anecdotal Text Teaching Materials Based on the TikTok Application for Class This research aims to develop anecdotal text teaching materials based on the TikTok application for class X2 students at Istiqlal Delitua Private High School. The methodology of this research is RND. The subjects in this research were class X2 students at Istiqlal Delitua Private High School. The data collection techniques are observation, documentation and tests. The assessment aspects used in this research are the appropriateness of the content of the anecdote text, the appropriateness of the structure of the anecdote text, the accuracy of words, the appropriateness of capital letter spelling and writing layout, criticism and humor. The research results show that the development of anecdotal text teaching materials based on the TikTok application for class X2 students at Istiqlal Delitua Private High School, especially anecdotal text material. The average obtained in general is in the very good category with a score of 90% from the media expert validation results, while from the results of the material expert validation the score is in the very good category with a score of 98% and from the results of student responses the score is in the good category, with a score of 82. 7% Thus, it can be concluded that the development of anecdotal text teaching materials based on the TikTok application for class